Distribution, vocalization and taxonomic status of hypsiboas roraima and h. angelicus (Amphibia: Anura: Hylidae) - Barrio-Amorós, César L.; Señaris, Josefa Celsa; Macculloch, Ross D.; Lathrop, Amy; Guayasamin, Juan M.; Duellman, William E. (Papéis Avulsos de Zoologia, 2011)
The distribution of the poorly known hylid frog Hypsiboas roraima Duellman & Hoogmoed, on the Guiana Shield is redefined, including new records from Venezuela. The advertisement call of this species is analyzed and Hypsiboas angelicus Myers & Donnelly is associated as a junior synonym of H. roraima.